PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK KARAKTER RELIGIUS SISWA DI MTS MAMBA'UL ULUM KARANGSARI BANTUR - Ismar Werisi; Zainuddin Fanani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the role of Islamic Religious Education (PAI) teachers in shaping students' religious character at MTs Mamba'ul Ulum Karangsari Bantur, the strategies implemented, and the supporting and inhibiting factors in its implementation. This research employed a qualitative approach with a descriptive research design. The study was conducted at MTs Mamba'ul Ulum Karangsari Bantur, located in Gumukmas Hamlet, Karangsari Village, Bantur District, Malang Regency, East Java. Data were collected through observation, interviews, and documentation, while data analysis was carried out using the stages of data reduction, data display, and conclusion drawing. The validity of the data was ensured through source triangulation and technique triangulation. The findings indicate that Islamic Religious Education teachers play a significant role in shaping students' religious character by serving as educators, mentors, role models, motivators, and supervisors. The strategies implemented include habituating religious activities such as collective prayers, Qur'an recitation, congregational prayers, providing advice, demonstrating exemplary behavior, and supervising students' conduct. Supporting factors include the school's religious culture, a supportive community environment, and collaboration among teachers and the madrasah. Meanwhile, inhibiting factors include the inconsistency of some students, the influence of technology and social media, and differences in students' family backgrounds. The study concludes that the development of students' religious character can be achieved effectively through consistent collaboration among schools, families, and the community.